Simulation Model of Traffic Jam at Crossroads - Mladen Kalajžić; Katica Miloš; Mirela Muić (Promet (Zagreb), 2002)
Traffic congestion is one of the major problems in most cities.It is the consequence of unavoidable motorization, butalso, in many cases, of improper solutions considering constructionof roads or organisation of traffic.This paper deals with one problematic crossroad in thetown of Zadar in which traffic jams occur due to poor organisationof traffic. Using mathematical simulation, the first partproves that traffic jams will certainly occur, and in the secondpart, crossroads signalling is considered as a possible solutionwhich, if combined with intelligent control could significantlyimprove the organisation of traffic at this crossroads.